An Analysis of learning difficulties faced by first year students of STMIK Palangkaraya in English Subject as General Course - Catharina Elmayantie; Norhayati Norhayati (ENLIT, 2021)
At the College of Informatics and Computer Management (STMIK) Palangka Raya, English course appear in the curriculum of each study programs. This course is divided into English I and English II, for both undergraduate and diploma levels. One of the goals of learning English here is so that students have the ability to speak English both verbally and in writing. The mastery level of English skill will be very beneficial for the students to comprehend their major subject; technology informatics and computers. As in the perspective of academic achievement for English courses, the students can be categorized at good level. As for the final assessment of a student, it is assessed by the level of attendance for each lecture, individual and group assignments, and test scores taken form midterm test and final test. One of the problem faced both teachers and students in teaching learning English that the lecturers have not been able to provide learning and assessment comprehensively for listening skill mastery. As the impact the students get less opportunity to practice listening skill. It is caused that the college does not yet have adequate supporting facilities such as language laboratory.